Management control packages in family businesses: a configurational approach - Stefanie Einhorn; Xaver Heinicke; Thomas W. Guenther (Journal of Business Economics, 2020)
This study uses survey data from top managers to explore how operational (e.g., cost types and cost center accounting) and strategically oriented (e.g., strategic and business planning) management accounting (MA) practices, diagnostic and interactive use of performance measures, and cultural controls are combined (management control package) to achieve high firm performance in family businesses (FBs). In previous research, such management control (MC) packages have received limited attention even though they offer an opportunity to reveal more information on the adoption of MA practices, use of performance measures, and MCs in FBs than analyses of individual control mechanisms. We chose a qualitative comparative analysis (QCA) because this method allows for explicitly addressing the three major challenges of configurational theory: asymmetry, conjunctional causation, and equifinality. By applying QCA, our study identifies six equifinal MC packages (i.e., different configurations of MA practices, types of use, and cultural controls with similar associations with firm performance) and, thus, provides an exploratory approach to describe more complex MA and MC designs that are empirically observable. By further analyzing these MC packages with additional information on the intensity of competition, the intensity of attention focusing, the interpretation of information by top management, and the organizational culture, this study extends the existing literature on FBs. The key finding of our analysis is that, regardless of their business environment, successful FBs place a very strong emphasis on cultural controls and/or have a high degree of interactive use of performance measures to steer their business.
Keywords: M10; M14; M21; M41; 650; Management control package; Family business; Configurational research; Qualitative comparative analysis; Firm performance